The Problems of Implementing Imkan Rukyat in the Case of an Invisible Hilal (Crescent): A Perspective of Syafi’i Scholars - Hudi Hudi; Ahmad Rofiq (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2023)
Imkan rukyat refers to the conditions under which the new moon (hilal) can likely be sighted based on specific criteria. When the hilal is visible, the following day can be confirmed as the start of the new lunar month. However, if the hilal is not seen during the rukyat observation, a dilemma arises between two choices: whether the next day should be declared as the first day of the new lunar month based on the criteria of imkan rukyat, or whether the current month should be completed (istikmal) to a full 30 days. All Islamic mazhabs including Hanafi, Maliki, and Hanbali generally advocate for istikmal if the hilal is not sighted. However, within the Syafi’i Mazhab, there is a divergence of opinion, with some scholars advocating for istikmal and others for hisab (astronomical calculations). This duality of opinion is particularly relevant in Indonesia, a country with a majority of Syafi’i followers. The aim of this research is to analyze the views of Syafi’i scholars on this matter. This study is a type of library research, focusing on the decisions of the Ministry of Religious Affairs of the Republic of Indonesia's isbat meetings regarding the start of the lunar month and the moon sighting data provided by Nahdlatul Ulama. The research is grounded in the Quran, Hadith, and Syafi’i jurisprudence (fiqh) texts. The findings of this study indicate that the majority of Syafi’i scholars hold that if the hilal is in a position of imkan rukyat but is not sighted, the month should be completed to 30 days (istikmal). However, some Syafi’i scholars permit the determination of the start of the new lunar month the next day based on hisab imkan rukyat, provided that the calculation is done by at least seven qualified astronomers who are unlikely to err, and that the non-sighting of the hilal is due to technical or natural factors. These results can serve as a reference for determining the start of the lunar month when the hilal is not visible due to cloudy conditions